Violence and Mental Illness - Rueve, Marie E. (Matrix Medical Communications, 2008)
Violence attracts attention in the news media, in the entertainment business, in world politics, and in countless other settings. Violence in the context of mental illness can be especially sensationalized, which only deepens the stigma that already permeates our patients’ lives. Are violence and mental illness synonymous, connected, or just coincidental phenomena? This article reviews the literature available to address this fundamental question and to investigate other vital topics, including etiology, comorbidity, risk factor management, and treatment. A psychiatrist who is well versed in the recognition and management of violence can contribute to the appropriate management of dangerous behaviors and minimize risk to patients, their families, mental health workers, and the community as a whole.